Descriptive Analysis in Teachers’ Perception in Teaching Reading With Problem-Based Learning - Rahayu, Sukma (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Reading skills are essential to enhance students' reading habits generally, especially when reading English-language materials. However, students still have difficulties in mastering reading skills. Therefore, appropriate learning methods are needed to improve students' reading skills. This study intended to analyze the teachers’ perception in teaching reading with problem-based learning and the challenges faced by the teacher during implementing of problem-based learning in teaching reading at junior high school. This research used qualitative descriptive research using two methods: interview and survey. The subjects of this study were 3 teachers in junior high school.  Data analyze consist of data reduction, data display, and conclusion drawing. Based on survey and interview sessions, it was found that the teachers’ perception of implementing of problem-based learning in teaching reading has positive sign. It is showed from the result of questionnaire given to the three English teacher. And for the challenges faced by the teacher during implementing of problem-based learning in teaching reading such as related to the topic that not too interesting for students, teacher who dominant the group discussion, and dysfunctional group.